Development of STEM Based Physics E-Modul with Virtual Lab to Improve Learning Outcomes - Muhammad Dzaki Fuad Salim Putra; Bambang Subali; Putut Marwoto (Universitas Negeri Semarang, 2025)
The Merdeka curriculum organizes the physics subject into concept understanding and science process skills. However, based on interviews and observations at MAN IC Pekalongan, the development of process skills in physics learning is rarely facilitated due to the limited availability of learning media and time. This RnD research aims to develop digital learning media as an alternative solution to these problems. The analysis of learning media needs showed that teachers and students need Interactive E-Modules as learning media, applications of physics in everyday life such as STEM, and a Virtual Lab packaged with interactive and simple language. The E-Module was validated by several experts in material, learning media, and learning and was declared highly feasible with an average score of 4.5 out of 5. The posttest results showed an average score of 59.67 for both the experimental and control classes. The n-gain analysis demonstrated that the E-Module effectively improved conceptual understanding, with an n-gain value of 0.74 (high), and had a positive effect on process skills with an average value of 87.86 for the experimental class and 86.44 for the control class, with a significance value of 0.032 in the independent sample test of both classes.